PENGARUH SUPLEMENTASI KONSENTRAT DALAM RANSUM TERHADAP PERFORMA, BOBOT KARKAS DAN NON KARKAS LANDAK JAWA (HYSTRIX JAVANICA F. CUVIER, 1823) - Farida, Wartika Rosa; Tjakradidjaja, Anita S.; Sari, Andri Permata (Perhimpunan Biologi Indonesia, 2012)
The Effect of Concentrate Supplementation in The Ration on Performance, Carcass and Non-Carcass Weight of Javan Porcupine (Hystrix javanica F. Cuvier, 1823). This study was conducted at Small Mammal Captivity, Zoology Division, Research Center for Biology,Indonesian Institute of Sciences, Cibinong, Bogor Regency. Eight porcupines consisted of 6 females and 2 males were used to know the effect of concentrate supplementation in the ration on performance, carcass and non carcass weight of javan porcupine. Ration treatment consisted of control ration (PI) and control ration plus concentrate comersial such as koi fish pellet (PII).Four porcupines (3 female and 1 male) were given control ration (PI) and three porcupines (3 female and 1 male) were given ration PII. A completely randomized design was used in this research. Data collected were nutrient consumption, average daily gain, feed conversion, slaughter weight, weight of cascass and non-carcass. The data were analyzed by analysis of variance. The result showed supplementation of koi fish pellet in the ration didn?t significantlyinfluence (P>0.05) performance of javan porcupine, but significantly (P<0.05) increase consumption on calcium and phosphor. Weight and percentage of carcass and non-carcass of javan porcupine were not affected by ration treatment. Average of weight and percentage of porcupine?s carcass of PI were 4,505.08 g and 59.67% and those of PII were 3,957.55 g and 56.54%, while average of weight and percentage of porcupine?s non-carcass of PI were 2,979.05g and 39.46% and those of PII were 2,774.60 g and 39.64%.Keywords: Concentrate, ration, performace, carcass, non-carcass